Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376796
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Field Studies

Abstract: Figure 1. We explore whether field studies on public displays can be conducted in virtual reality. In two user studies we compare user behavior between a real public space (left) and a virtual public space (middle). For one study, we developed a gesture-controlled display for both environments (right).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 81 publications
(123 reference statements)
1
41
0
Order By: Relevance
“…The contribution of this paper is threefold: (1) We propose the idea of using Virtual Reality as a test-bed for usability and security evaluations of real-world authentication systems. (2) We complement prior work that evaluated usability aspects in VR [64,104] by the first lab-based in-VR usability evaluation and the first online security evaluation through recordings in VR of a real-world authentication system and validate the use of VR through a comparison with the real-world study [52]. (3) Finally, we derive lessons learned to support researchers in designing, developing, and evaluating authentication systems of similar type in VR and discuss potential follow-up research directions.…”
Section: Contribution Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of this paper is threefold: (1) We propose the idea of using Virtual Reality as a test-bed for usability and security evaluations of real-world authentication systems. (2) We complement prior work that evaluated usability aspects in VR [64,104] by the first lab-based in-VR usability evaluation and the first online security evaluation through recordings in VR of a real-world authentication system and validate the use of VR through a comparison with the real-world study [52]. (3) Finally, we derive lessons learned to support researchers in designing, developing, and evaluating authentication systems of similar type in VR and discuss potential follow-up research directions.…”
Section: Contribution Statementmentioning
confidence: 99%
“…While there are infrastructures that allow running online studies (e.g., Amazon Mechanical Turk) and result in valuable and inspiring privacy and security research [7,70,84,85], they are often not suitable for USEC research involving physical prototype systems. A promising emerging evaluation paradigm is Virtual Reality (VR) studies [64,89,104]. VR studies allow researchers to conduct evaluations by having participants experience virtual replicas of real-world systems in an immersive VR environment.…”
Section: Introductionmentioning
confidence: 99%
“…There are opportunities in experimenting with novel methodologies for evaluating pervasive displays. Recently, researchers have been investigating the use of virtual and augmented reality for evaluating ubiquitous systems, IoT devices, and security systems [14][15][16]. Most relevant to this special issue is the work of Mäkelä et al [14], which compared behavior of bystanders around public displays in the real world to their behavior around virtual displays in an immersive virtual environment.…”
Section: The Future Of Pervasive Displaysmentioning
confidence: 99%
“…Recently, researchers have been investigating the use of virtual and augmented reality for evaluating ubiquitous systems, IoT devices, and security systems [14][15][16]. Most relevant to this special issue is the work of Mäkelä et al [14], which compared behavior of bystanders around public displays in the real world to their behavior around virtual displays in an immersive virtual environment. They found that user behavior is largely similar across both settings, suggesting that conducting user studies in virtual reality can be a viable alternative to real world field studies which are typically difficult, expensive, and time-consuming.…”
Section: The Future Of Pervasive Displaysmentioning
confidence: 99%
“…He published 70+ papers related to HCI and publishes regularly at CHI. He is active in security and privacy for virtual reality [8][9][10] interaction in VR [19] and novel VR applications [21].…”
Section: Organizersmentioning
confidence: 99%